Evaluation of UV-B Ameliorating Properties of Indigenous Plants Ashwagandha Withania somnifera (Dunal), Amla Emblica officinalis (Gaertn), and Prickly Chaff Flower Achyranthes aspera (L.) Supplemented Diets in Prior UV-B Exposed Catla catla - Sharma, JaiGopal; Singh, Moirangthem Kameshwor; Chakrabarti, Rina (Frontiers in Marine Science, 2022)
Ultraviolet B (UV-B) radiation is a potent environmental stressor and it severely affects the survival, growth, and physiology of aquatic organisms. The UV-B protective properties of three herbal ingredients enriched diets were evaluated in pre-exposed Catla catla. Fish (70.38 ± 1.18 g) were divided into five sets with three replicates each. Four sets were exposed to UV-B (80 µW/cm2) for an initial 10 days (20 min/day), and the fifth one remained unexposed (control). On day 11, feeding with enriched diets started. These diets were: diet 1 (D1) containing Withania somnifera (0.5%) root powder, diet 2 (D2) containing Emblica officinalis (1.25%) fruit powder, diet 3 (D3) containing seeds of Achyranthes aspera (0.5%), and diet 4 (D4) control. There were two batches of D4 diet-fed fish, D4a, UV-B exposed, and D4b unexposed. Blood and tissue samples were collected on days 0, 7, 14, and 21 of feeding. The average weight reduced 26.32% in UV-B exposed catla compared to the unexposed one on day 0. Among the exposed fish, average weight was significantly higher in D3 compared to others throughout the study period. Significantly lower nitric oxide synthase (NOS) and higher thiobarbituric acid reactive substances (TBARS), carbonyl protein, superoxide dismutase (SOD), and heat shock proteins (Hsp) 70 and 90 were observed in D4a compared to the enriched diet fed catla. The NOS level was significantly higher in D3 on day 21. The TBARS level was significantly lower in D3 on days 7 and 14 and in D2 and D3 on day 21. The carbonyl protein, SOD, and Hsp70 levels were always significantly lower in D3 compared to others, and D2 followed D3 treatment. Hsp 90 was significantly lower in D2 compared to others on day 7 and in D3 on days 14 and 21. All three enriched diets helped the fish overcome the harmful effect of UV-B radiation, and the D3 diet-fed fish showed the best performance.